E-Transactions in Digital Era - R D Santy; G H Utomo (International Journal of Research and Applied Technology, 2021)
The purpose of this research is to help marketplace providers utilize E-commerce to improve their business. The method used in this study is a survey and literature study from research that has been done before. The results show that the role of the e-commerce market in online business transactions is useful to attract buyers. Starting from product marketing through media such as social media, websites, and advertisements. The role of E-commerce marketplace in online business transactions provides many benefits such as fast access to transactions, availability of goods, and ease of accessing the site.